APPLICATION OF GROUP GUIDANCE SERVICES TO INCREASE RESPONSIBILITY AND MATHEMATICAL LEARNING ACHIEVEMENTS (Study of Class IX SMP Negeri 06 Lebong) - Leni Suriyani; Nina Kurniah (UNIB Press, 2019)
This study aims to describe: (1) Group guidance services in increasing student responsibility; (2) Group guidance services in improving student learning achievement. The research method used is Classroom Action Research. The research subjects were 10 Lebong State Middle School 06 students. The technique of collecting data uses observation and documentation. The data analysis used was descriptive qualitative and quantitative descriptive. Based on the results and discussion of this study it can be concluded that: (1) Group guidance services can increase student responsibility. There is a significant increase in responsibility between the First Cycle, the Second Cycle, and the Third Cycle. The First Cycle the average student responsibility in the category is less, increasing to the category both in the Second and Third Cycles. (2) Group guidance services can improve student learning achievement. From the results of the study show how group guidance services can improve student learning achievement, it appears there is a significant increase in the percentage of mastery learning mathematics. In the First Cycle the percentage of completeness only reached 40%, and increased in the Second Cycle to 70%, and more increased to 90% in the Third Cycles.